Promoting good governance in sri lanka: a case for right to information (prospects and challenges) - Akurugoda, C. (University of Jaffna, 2012)
Right to Information is an essential requirement of good governance in a country. Since Sri Lanka is in a post war context, it is claimed that government decisions should focus on capacity development in the country. Sri Lanka faces enormous challenges in the areas of good governance, transparency, abuse of discretion and corruption. It is argued that it has become a necessity to enact a piece of legislation which is transparent oriented and further which enable people to be informed. In this context Sri Lanka should enact and implement a legislation to give effect to people’s Right to Information. This type of enactment will promote openness, transparency and accountability and shall act as a watch dog against abuse of power, corruption, and bureaucratic apathy. Further it will enhance the participatory democracy by enabling people to make an informed choice. Furthermore, sustainable development requires the sound decisions which have taken in the light of good governance. To serve this purpose transparency is the cardinal principle. Therefore ensuring that transparency through enacting Right to Information Act is paramount.
Keywords: Good governance; Participatory democracy; Right to information; Sustainable developmen